Організування та оцінювання маркетингової взаємодії підприємств на основі використання Інтернет-технологій - Угольков, Євгеній Олегович (Національний університет "Львівська політехніка", 2019)
Дисертацію присвячено вирішенню наукового завдання розроблення теоретичних положень та надання методико-прикладних рекомендацій з удосконалення маркетингової взаємодії з клієнтом підприємства з використання Інтернет-технологій. У роботі розвинуто понятійний та термінологічний апарат щодо взаємодії з клієнтом підприємства. Удосконалено класифікацію видів монетизації Інтернет-ресурсів. Удосконалено науково-методичний підхід до прогнозування трафіку Інтернет-ресурсу. Удосконалено параметри основних канали подання контенту на різних етапах взаємодії з клієнтом. Проведено детальний аналіз основних показників функціонування Інтернет-ресурсів на прикладі вітчизняних підприємств. Розроблено та апробовано модель об’єднуючого контент-забезпечення маркетингової взаємодії підприємства з клієнтом з розрахунком впливу контенту на рішення клієнта про купівлю на різних етапах взаємодії підприємства. Удосконалено систему показників оцінювання рівня економічної ефективності контенту за його впливом на прийняття рішень клієнтом про купівлю. Диссертация посвящена решению научной задачи разработки теоретических положений и предоставления методико-прикладных рекомендаций по совершенствованию маркетинговой взаимодействия с клиентом предприятия c использованием Интернет-технологий. В работе развит понятийный и терминологический аппарат по взаимодействию с клиентом предприятия. Усовершенствована классификация видов монетизации Интернет-ресурсов. Усовершенствована научно-методический подход к прогнозированию трафика Интернет-ресурса. Усовершенствована параметры каналов подачи контента на различных этапах взаимодействия с клиентом. Проведен детальный анализ основных показателей функционирования Интернет-ресурсов на примере отечественных предприятий. Разработана и апробирована модель объединяющего контент обеспечения маркетингового взаимодействия предприятия с клиентом с расчетом влияния контента на решение клиента про покупку на разных этапах взаимодействия с ним. Усовершенствована система показателей оценки уровня экономической эффективности контента с его влиянием на принятие клиентом решений о покупке. The dissertation is devoted to solving the scientific problem of developing theoretical bases and providing methodological and applied recommendations for improving marketing interaction with the client of the company with the use of Internet-technologies. The urgency of scientific research is due to an increase in the intensity of the use of the Internet as the main channel of interaction between the enterprise and the client, as well as establishing connection between online and offline interaction with the client within the enterprise. The object of research of the dissertation is the marketing interaction of the enterprise with the client, and the subject of the study are theoretical, methodological and applied bases for developing marketing interactions by using Internet technologies. The conceptual and terminological apparatus on cooperation with the client of the enterprise is developed, namely, the author's typology of Internet resources users is given, the concept of "Internet resource traffic", "Internet resource monetization", "customer journey", "separate and unifying content supply" etc are defined. The different terms of "monetization" are considered to better understand their differences. The term "lead", "lead generation" has been clarified, that allowed to combine the traditional classification of the company's clients with the current practice of interaction with clients on enterprises using Internet technologies. Classification of types of monetization of Internet resources was improved through the introduction of additional signs as timeliness and form of payment that allow to better understand the monetization of Internet resources of enterprises and, in accordance with this, to adjust managerial decisions. This signs gives the better understanding of differences in interactions of enterprises of different economy sectors. Content channels parameters have been expanded at various stages of interaction with clients. Based on the generalization of these channels, a standardized list was proposed and key characteristics such as the frequency of content transmission, the ability to make changes and the stage of interaction of the enterprise with the client were introduced. The advanced features of content channels allow marketers to better understand what content is at what stage and how often it is being prepared to interact with the customer, as well as improve that engagement by focusing on the focus and content of the individual stages of engagement. The development of such a classification of channels has allowed creating the basis for building the author's own model of unifying content supply model for interaction with clients, which actually considers the concept of customer journey in accordance to preparation and presentation of relevant content at all stages of interaction between the enterprise and the client. Unifying content supply model to ensure enterprise marketing interactions with the customer includes the main stages: identifying target customers, customer engagement, sales and partnerships. The author highlights important elements of customer interaction, namely responsible departments, the type of content being transmitted, and the tools by which the client interacts at each stage. The ways to combine online and offline business interaction with a customer to maximize customer satisfaction and make a positive purchasing decision are developed.. The system of indicators of estimation of level of economic efficiency of content on its influence on decision-making by the client on purchase is improved The model has been tested in the practice of domestic enterprises by improving the marketing tools of their interaction with customers The scientific and methodological approach to the forecasting of Internet resource traffic is improved. A detailed analysis of the main indicators of the functioning of Internet resources is conducted on the example of web stores of domestic enterprises. The applied Pearson correlation coefficient allowed identifying clear relationships that point to the high level of importance of content in the functioning of domestic Internet resources. The multivariate regression analysis also confirmed this correlation. To effectively monetize customer interactions the recommendations about development of a portrait of the customer was made. This also allows to understand better clients’ motivations and use the “customer journey” concept. Additionally, an analysis of the choice of the content language of the Internet resource allowed developing the recommendations of the use of the Ukrainian language in Internet resources, and the consequences of refusing to use it as the main language of Internet resources. The practical significance of the results obtained in the dissertation is the ability of marketers, digital marketers, managers and owners of enterprises to use methodological recommendations for: monetization of Internet resources; the use of the typology of users of Internet resources; the practical application of Internet marketing tools in accordance with the goals and objectives of the enterprise; the choice of content channels and the construction of a unifying content supply of the interaction of the enterprise with their client. The developed model allows marketers, managers and business owners to build a unified content system to ensure the interaction of the enterprise with the client through the use of modern Internet technologies and the creation of a unified responsible structural department in the enterprise. In addition, research results provide a solid basis for further research in this area and improve the interaction of the company with the client through the use of Internet technologies, which are changing rapidly today.
Организация и оценка маркетингового взаимодействия предприятий на основе использования Интернет-технологий
Organization and evaluation the marketing interactions of enterprises using Internet-technologies
Keywords: маркетингова взаємодія; інструменти Інтернет-маркетингу; монетизація Інтернет-ресурсу; об’єднуюче контент-забезпечення; організування; оцінювання; маркетинговая взаимодействие; инструменты Интернет-маркетинга; монетизация Интернет-ресурса; контент; объединяющее контент обеспечения; marketing interaction; tools of Internet marketing; monetization of the Internet resource; content; unifying content supply